Insurance literacy, perceived trust and insurance inclusion in Uganda - Archillies Kiwanuka; Athenia Bongani Sibindi (Management Matters)
Purpose – This study primarily aimed to explore how insurance literacy and perceived trust interact to affect insurance inclusion in Uganda. Through this, we aimed to determine whether perceived trust serves as a mediator in the relationship between insurance literacy and insurance inclusion. Design/methodology/approach – This research employed a correlational, cross-sectional and quantitative approach. A total of 400 voluntarily insured individuals in Uganda were sampled. Structured survey questionnaires were employed for data collection. PLS-SEM with bootstrapping was used to examine the hypothesized relationships. Findings – The findings indicated a significant, positive correlation between insurance literacy with both insurance inclusion and perceived trust. Furthermore, perceived trust was identified as having a positive and significant impact on insurance inclusion in Uganda. Perceived trust was also established as a significant mediator in the connection between insurance literacy and insurance inclusion in the context of Uganda. Originality/value – The contribution of this research resides in its explanation of how insurance literacy influences insurance inclusion in Uganda. For insurance literacy to influence insurance inclusion, a significant portion of insurance literacy is mediated through perceived trust of insurance providers.